Tertiary Students’ Perceptions of Learning Oral Presentation Skills in In-Class and Online Learning Environment: A Case Study - Noor Raha, Mohd Radzuan; Wan Jumani, Fauzi; Hamizah, Zahari; Marziah, Ramli (Universiti Kebangsaan Malaysia, Malaysia, 2023)
Online learning is seen to be the solution to education throughout the Covid-19 pandemic. Instructional sessions and assessments are conducted in the virtual setting which affects instructors and students alike. Oral assessments like presentation sessions are conducted on teleconferencing platforms which bring different dimensions in pedagogy and online learning strategies employed by students. Thus, this study aimed to determine undergraduates’ perceptions of online and in-class presentations. These undergraduates went through remote learning sessions and were not physically campus bound. For this study, the mixed-method approach was adopted and a set of questionnaires with two open-ended questions was distributed online to 1187 Universiti Malaysia Pahang (UMP) undergraduates who were enrolled in the English for Professional Communication (UHL2432) course for Semester 2, session 2020/2021. Quantitative data were collected, and the descriptive statistics were calculated. The findings revealed students’ mixed perceptions towards the effectiveness of applying delivery skills and elements of professionalism in online and in-class oral presentations. Furthermore, although findings have shown that students have adapted to online learning and preferred certain elements of oral presentation in a virtual environment, they also indicated that students preferred to learn oral presentations in a face-to-face classroom. Students’ mixed perceptions were due to challenges in aspects such as maintaining eye contact, projecting voice, using visual aids, gestures and postures as well as interacting with the audience virtually. The findings of this study will provide a useful guide for the enhancement and development of online teaching and learning methodologies.